2023
DOI: 10.1111/cns.14263
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion tensor imaging‐based machine learning for IDH wild‐type glioblastoma stratification to reveal the biological underpinning of radiomic features

Abstract: IntroductionThis study addresses the lack of systematic investigation into the prognostic value of hand‐crafted radiomic features derived from diffusion tensor imaging (DTI) in isocitrate dehydrogenase (IDH) wild‐type glioblastoma (GBM), as well as the limited understanding of the biological interpretation of individual DTI radiomic features and metrics.AimsTo develop and validate a DTI‐based radiomic model for predicting prognosis in patients with IDH wild‐type GBM and reveal the biological underpinning of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“… 7 , 8 The advancements in radiogenomics have uncovered associations between radiomic features from multimodal magnetic resonance imaging (MRI), such as conventional MRI, perfusion‐weighted imaging (PWI), and diffusion tensor imaging (DTI), and the underlying biological processes in gliomas. 9 , 10 , 11 , 12 Improved understanding of the biological interpretation of radiomic features at the molecular level could potentially accelerate the development of personalized medicine. 13 However, radiogenomics studies on prognosis assessment of insular gliomas have not yet been reported.…”
Section: Introductionmentioning
confidence: 99%
“… 7 , 8 The advancements in radiogenomics have uncovered associations between radiomic features from multimodal magnetic resonance imaging (MRI), such as conventional MRI, perfusion‐weighted imaging (PWI), and diffusion tensor imaging (DTI), and the underlying biological processes in gliomas. 9 , 10 , 11 , 12 Improved understanding of the biological interpretation of radiomic features at the molecular level could potentially accelerate the development of personalized medicine. 13 However, radiogenomics studies on prognosis assessment of insular gliomas have not yet been reported.…”
Section: Introductionmentioning
confidence: 99%